Le festin dahoméen. Femmes du palais, politiques internes et pratiques culinaires en Afrique de l’Ouest au XVIIIe-XIXe siècle - J. Cameron Monroe; Anneke Janzen (Afriques)
Feasting is a central component of elite power strategies in complex societies worldwide. In the precolonial Kingdom of Dahomey, located in the Republic of Bénin, public feasts were a critical component of royal strategies to attract and bind political subjects over the course of the 17th through 19th centuries, a period of dramatic political transformation on the Bight of Benin. Archaeological excavations within the domestic quarters of a series of Dahomean royal palace sites have yielded diverse faunal and ceramic assemblages that represent clear examples of 1) ritualized food consumption and 2) everyday culinary practices. In this paper, faunal and ceramic evidence from two excavated contexts is marshaled to distinguish the archaeological signatures of feasting in Dahomey, highlighting the importance of private feasts in attempts to build political influence in the domestic zones of Dahomean royal palaces. In particular, this analysis foregrounds how palace women jockeyed for power and influence during a period of political uncertainty.